2014
DOI: 10.1093/rheumatology/keu035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL-6 and IL-6 blockade on neutrophil function in vitro and in vivo

Abstract: Therapeutic blockade of IL-6, while inducing a transient neutropenia, does not directly affect neutrophil functions associated with host defence. TCZ-associated neutropenia cannot be explained by direct induction of apoptosis by TCZ, induction of apoptosis following depletion of IL-6, nor increased phagocytosis of neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 23 publications
11
113
2
5
Order By: Relevance
“…In MONARCH, changes in laboratory values in the sarilumab group, including neutropenia, liver transaminases and total cholesterol, were expected class effects. While the mechanism of neutropenia remains unclear, studies have shown that blockade of IL-6R does not affect neutrophil function 34. This is consistent with MONARCH and previous sarilumab studies,24 25 demonstrating that decreased neutrophil counts were not associated with a concurrent increase in infection rate.…”
Section: Discussionsupporting
confidence: 85%
“…In MONARCH, changes in laboratory values in the sarilumab group, including neutropenia, liver transaminases and total cholesterol, were expected class effects. While the mechanism of neutropenia remains unclear, studies have shown that blockade of IL-6R does not affect neutrophil function 34. This is consistent with MONARCH and previous sarilumab studies,24 25 demonstrating that decreased neutrophil counts were not associated with a concurrent increase in infection rate.…”
Section: Discussionsupporting
confidence: 85%
“…In a primate model of arthritis managed with TCZ, the absence of bone marrow myeloid hyperplasia or hypoplasia when ANC was reduced and the lack of neutrophil morphological abnormalities strongly suggested that neither peripheral sequestration nor incomplete granulopoiesis was the underlying mechanism of the reduced circulating neutrophils [30]. A recent study [7] of neutrophil function and survival, which included RA patients treated with TCZ in an open-label, phase 4 trial, demonstrated that TCZ treatment did not have a direct effect on neutrophil functions, including apoptosis, phagocytosis, respiratory burst, chemotaxis or expression of adhesion molecules. In vitro evidence suggests that IL-6 increases circulating neutrophils by releasing them from marginated pools in bone marrow [8].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased neutrophil counts have been reported in trials of TCZ in RA patients [13, 14]. Blocking IL-6 signalling with TCZ is associated with transient neutropenia, but ex vivo findings show this does not directly affect neutrophil functions associated with host defence [7]. …”
Section: Introductionmentioning
confidence: 99%
“…While LPS, GM-CSF, IL-8, and LTB 4 have been found to extend neutrophil lifespan in vitro , PAF, fMLF, and IL-6 show no effect, and TNFα shows a biphasic response where it promotes apoptosis during the first 8 h of exposure, followed by a delayed rate of apoptosis at later times (Klein et al, 2000, 2001; Cowburn et al, 2002; Liu et al, 2005; Wright et al, 2014). Primed neutrophils from patients with multiple sclerosis, ANCA-associated vasculitis, and liver cirrhosis show increased apoptosis (Harper et al, 2001; Klimchenko et al, 2011; Naegele et al, 2012), while neutrophils from patients at risk of multiple-organ failure and individuals presenting with septic peritonitis, severe trauma, or septic trauma show a decrease in apoptosis (Ertel et al, 1998; Biffl et al, 1999, 2001; Nolan et al, 2000; Feterowski et al, 2001).…”
Section: Phenotypic Changes During Primingmentioning
confidence: 99%